Donation-Based Crowdfunding During Covid-19 Pandemic - Yuni Nustini; Tiyas Kurnia Sari (Management Institute Faculty of Economics Universitas Andalas, 2023)
This study aims to determine the factors that influence the decision to donate through crowdfunding. The factors studied include the ease of the system, religiosity, social spirit, reputation, security, and influencers with trust in management as a mediating variable and their influence on the decision to donate through crowdfunding. This study adopted the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) to develop the research model. The sample in this study amounted to 300 respondents with a convenience sampling technique. Primary data that is processed comes from answers to questionnaires distributed to respondents via Google Forms. Data were analyzed using the statistical software Smart PLS Version 3.3.5. The results of this study indicate that the ease of the system and trust have an influence on the decision to become a donor on the crowdfunding platform. Religion and social spirit do not influence the decision to become a donor on the crowdfunding platform. Reputation, security and influencers influence the trustworthiness of managing a crowdfunding platform.